Pengaruh Literasi Keuangan, Inklusi Keuangan, dan Brand Image Terhadap Penggunaan Layanan Digital Perbankan Syariah: Studi Kasus Mahasiswa FAI UMSU - Indah Rezqi Vitria Ma; Syahrul Amsari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The market share in the world of sharia banking, specifically in Indonesia, is still lower than in conventional banking, even though sharia banking has made efforts for convenience and comfort for its customers, one of which is through digital technology-based services. This is caused by many factors, and because the aim of this research is to determine and assess the influence of independent factors such as Financial Literacy (X1), Financial Inclusion (X2), Brand Image (X3) on the dependent variable, namely the use of digital sharia banking services. (Y) . This research uses a quantitative approach with sampling carried out using a simple random sampling technique. The main data used in this research comes from surveys filled out directly by respondents. The population of this study was 1500 students from the Faculty of Islamic Religion, Muhammadiyah University of North Sumatra, with a total sample of 94 people. The analytical tools used are several linear regression analyses. The research results show that financial literacy has no significant effect on the use of sharia banking digital services with a significant value of 0.319, Financial Inclusion partially has a significant effect on the use of sharia banking digital services with a significant value of 0.047, while Brand Image has a significant effect on the use of digital services with a significant value 0,000.